Proxies of community production derived from the diel variability of particulate attenuation and backscattering coefficients in the northwest Mediterranean Sea - Barnes, M.; Antoine, David (American Society of Limnology and Oceanography, Inc., 2014)
A 6 yr time series of high frequency inherent optical property (IOP) measurements in the Mediterranean was used to derive information on the diel and seasonal variability of particulate production. Empirical relationships between particulate attenuation (cp), particulate backscattering (bbp), and particulate organic carbon allowed calculation of estimates of net community production (NCP), daytime NCP (NCPd), and gross community production (GCP) from the diel variations in either IOP. Similar seasonal variations and good correlation (r = 0.83, p < 0.001) between daily means of cp and bbp were observed, yet differences in the timing and amplitude of their diel cycles led to significant differences in their derived production metrics. Best agreement was obtained during bloom proliferation (44.1–66.7% shared variance) when all three production estimates were highest, while worst was during bloom decline. Best overall correlation was found for NCPd. Accordingly, only cp-derived estimates reproduced predicted seasonal variations in community production and seasonality of ‘‘traditional’’ chlorophyll-based primary production models. Analysis of the diel cycles of ‘‘real-time’’ net community production (NCPh), determined from the first-derivative of either cp or bbp, revealed ca. fourfold to eightfold lower daytime NCPh, twofold to fivefold lower daily maximum NCPh, and twice as much intraseasonal variability relative to the mean amplitude of diel variations for bbp. Although the timing of maximum of cp-derived NCPh was consistently prior to solar noon, significant seasonal differences in the timing of maximum bbp-derived NCPh was observed. Particulate backscattering may be used to infer biogeochemical properties, while greater understanding of the diel cycles of bbp is needed before bbp can be used to investigate daily community production